Peran work engagement dan social support terhadap innovation work behavior tim startup. (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract All members of the startup team have the responsibility to always have innovative behavior in any field of work. That is because if startups want to continue to exist, these startups must always innovate to create new and useful products for customers. The purpose of this study is to determine the relationship between work engagement and social support with innovation work behavior among startup team members at the Airlangga University business incubator. The subjects in this study were 45 members of the startup team consisting of startup founders and members. The data collection tool used is the innovation work behavior scale based on the theory from Janssen (2000). The results of hypothesis testing using multiple linear regression obtained an F value of 16.494 with a significance of p = 0.000 (p <0.01). So it can be concluded that there is a relationship between work engagement and social support with innovation work behavior. Keywords: Startup, Work Engagement, Social Support, Innovation Work Behavior Abstrak Seluruh anggota tim startup memiliki tanggung jawab untuk selalu memiliki perilaku inovasi baik itu dalam bidang pekerjaan apapun. Hal itu dikarenakan apabila startup ingin tetap eksis, startup tersebut harus selalu berinovasi untuk membuat produk yang baru dan bermanfaat bagi pelanggan. Tujuan dari penelitian ini yaitu untuk mengetahui hubungan antara work engagement dan sosial support dengan innovation work behavior pada anggota tim startup di inkubator bisnis universitas airlangga. Subjek dalam penelitian ini adalah 45 anggota tim startup yang terdiri dari founder dan anggota startup. Alat pengumpulan data yang digunakan yaitu skala innovation work behavior berdasarkan teori dari Janssen (2000). Hasil uji hipotesis menggunakan regresi linier ganda diperoleh nilai F sebesar 16.494 dengan signifikansi p = 0.000 (p<0.01). Dapat disimpulkan bahwa ada hubungan antara work engagement dan sosial support dengan innovation work behavior. Kata kunci: Startup, Work Engagement, Social Support, Innovation Work Behavior